Parameters Used With Diode Lasers (808-980 nm) in Dentin Hypersensitivity Management: A Systematic Review - Abdelkarim-Elafifi, Haitham; Parada Avendaño, Isabel; Arnabat Domínguez, Josep (Journal of Lasers in Medical Sciences, 2022)
Introduction: The present study aimed to describe parameters used with 808- to 980-nm wavelength diode lasers for managing dentin hypersensitivity and analyze their results. Methods: The inclusion criteria were based on randomized controlled clinical trials using diode lasers at an 808-980 nm wavelength range in patients with dentine hypersensitivity with a minimum of 1-month follow-up. An electronic search for articles on Medline, PubMed, and Cochrane databases was performed. The risk of bias was assessed with the Cochrane collaboration tool. Results: Our electronic search resulted in 130 papers, of which 11 articles met the inclusion criteria. A majority of the studies assessed dentine hypersensitivity using the Visual Analogue Scale, which ranged between 2.3 and 8.8 before treatment and significantly reduced to a mean value of 0.45-3.7 after diode laser application. The power settings ranged between 1.5 mW and 3 W with an emission mode of continuous wave, except for 2 authors who used chopped mode. The energy density varied from 2.5 to 128 J/cm2, and the exposure time was between 10 and 120 seconds. The authors applied a minimum of 1 to 4 treatment sessions with a 2-day to 1-week interval between them. Most of the studies mentioned the tooth surface as the treatment site but without describing the specific irradiation points. Conclusion: Despite the heterogeneity of the analyzed variables, a statistically significant improvement in all laser groups as described. However, they cannot be compared homogenously. Doi:10.34172/jlms.2022.03.